2004
DOI: 10.1182/blood.v104.11.4873.4873
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosomal Pattern 14q-Translocation Plus 13q-Deletion Is Characteristic for Multiple Myeloma after a Preceding Monoclonal Gammopathy of Undetermined Significance.

Abstract: Multiple myeloma (MM) may be preceded by a monoclonal gammopathy of undetermined significance (MGUS), but it is at present unclear whether or not MM post-MGUS is biologically and clinically different from MM de-novo. To address this issue, we have performed a molecular cytogenetic analysis of 32 cases of MM post-MGUS (median time between recognition of MGUS and transition to MM, 7.6 years; range, 2.6 years to 19.5 years) and compared the findings with those of 256 patients with MM de-novo, in whom no previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to our recent findings, the cytogenetic pattern of a 14q‐translocation plus del(13q14) is a characteristic chromosomal finding in MM post‐monoclonal gammopathy of undetermined significance (MGUS)‐(20, 21). However, there were no significant differences between the three MM patient cohorts regarding the frequency of the 14q‐translocation plus del(13q14) pattern (21% in Group A, 32% in Group B, and 15.6% in Group C; P > 0.45).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to our recent findings, the cytogenetic pattern of a 14q‐translocation plus del(13q14) is a characteristic chromosomal finding in MM post‐monoclonal gammopathy of undetermined significance (MGUS)‐(20, 21). However, there were no significant differences between the three MM patient cohorts regarding the frequency of the 14q‐translocation plus del(13q14) pattern (21% in Group A, 32% in Group B, and 15.6% in Group C; P > 0.45).…”
Section: Resultsmentioning
confidence: 97%
“…Although detailed data are not available on the frequency of MGUS prior to MM, elderly MM patients are more likely to have a disease that evolved from a long‐lasting, pre‐existing MGUS than young MM patients. We have recently observed that the simultaneous occurrence of a 14q‐translocation with a del(13q14) is a characteristic chromosomal pattern in MM patients after a preceding MGUS (21). We therefore included these chromosomal abnormalities as well as chromosomes associated with hyperdiploidy in the present analysis.…”
Section: Discussionmentioning
confidence: 99%